PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH TERHADAP KINERJA GURU DAN KARYAWAN DI SMK ISLAM ANDALUS JAKARTA SELATAN - Diva Kanya Putri; Indi Nervilia; Sendianto . (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Wiraraja, 2026)
This study investigates the effect of the principal’s transformational leadership style on teacher performance at SMK Islam Andalus, South Jakarta. The study was conducted to address the issue of how leadership influences teachers’ work performance in achieving educational goals. The research aimed to determine the magnitude of the influence of transformational leadership on teacher performance. A quantitative approach was employed using a total sampling technique, involving all 30 teachers and staff as respondents. Data were analyzed using regression and hypothesis testing. The results showed a positive and significant effect of transformational leadership on teacher performance, with the regression equation Y = 8.384 + 0.718X and a t-value of 6.863, exceeding the critical value of 1.697. The coefficient of determination indicated that transformational leadership contributed 79.6% to teacher performance, while the remaining 20.4% was influenced by other factors. These findings suggest that effective transformational leadership plays a crucial role in improving teacher performance.